Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1614/ipsm-d-12-00059.1
|View full text |Cite
|
Sign up to set email alerts
|

No Long-Term Effects of Prescribed Fire on Lehmann Lovegrass (Eragrostis lehmanniana)–Invaded Desert Grassland

Abstract: Desert grasslands of the southwestern United States have experienced an increase in the abundance and distribution of woody plant species over the past century. Shrub encroachment has caused a substantial loss of grasslands in the northern Chihuahuan Desert. The Chihuahuan Desert has also been invaded by Lehmann lovegrass, a fire-adapted species from southern Africa. In 1999, the U.S. Department of Agriculture–Agricultural Research Service burned a remnant desert grassland to determine the effects of prescribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…48,51 Fuel treatments caused a reduction, 49,53 as well as no changes to invasive species abundance. 42,43,47,54,55 Similar to invasive species, woody plant species have increased in abundance along the US-Mexico border over the past several decades, including in areas previously occupied by grasslands. 56,57 Woody plant encroachment can increase the risk of a high severity fire, and several studies addressed treatments to reverse this pattern and help restore a low-severity fire regime.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48,51 Fuel treatments caused a reduction, 49,53 as well as no changes to invasive species abundance. 42,43,47,54,55 Similar to invasive species, woody plant species have increased in abundance along the US-Mexico border over the past several decades, including in areas previously occupied by grasslands. 56,57 Woody plant encroachment can increase the risk of a high severity fire, and several studies addressed treatments to reverse this pattern and help restore a low-severity fire regime.…”
Section: Resultsmentioning
confidence: 99%
“…48,51 Fuel treatments caused a reduction, 49,53 as well as no changes to invasive species abundance. 42,43,47,54,55…”
Section: Resultsmentioning
confidence: 99%
“…Eragrostis lehmanniana is an exotic invasive perennial grass species common in the desert Southwest ecoregion, which was introduced to the Sonoran Desert in the early–mid 20th century as cattle forage to replace overgrazed native grasses and halt erosion. Eragrostis lehmanniana may be considered a less impactful invasive than the exotic annual grasses of the region, or the other common invasive perennial grass Cenchrus ciliaris , due to its relative palatability, and co‐existence with some native species in post‐fire conditions (lack of a true grass/fire cycle; McDonald & McPherson, 2011; McGlone, 2013). Although not correlated with fire recency, it seems likely Eragrostis lehmanniana was able to establish within the study plots after the fires, as it was first recorded in the 2007 survey.…”
Section: Discussionmentioning
confidence: 99%
“…Tormo et al (2015) reported that L. lactis was the dominant species in raw goat milk. However, some studies reported that L. lactis was the causal agent of postharvest decay of mushroom (Zhao et al, 2013(Zhao et al, , 2018. Furthermore, L. lactis had a homofermentative metabolism, and it does not directly cause soft rot, but it can produce lactic acid from carbohydrates and create favorable conditions for soft rot symptoms of various vegetables (Baheyeldin and Gahan, 2010;Song et al, 2017).…”
Section: Native Microflora Composition and Diversitymentioning
confidence: 99%
“…Rodrigues et al (2016) suggested that the Lactococcus is a potential etiological agent in mastitis outbreak. Zhao et al (2013) showed that the pathogen causing postharvest water-soaked and sunken lesions on the stipes and decay of Pleurotus eryngii was isolated and identified as L. lactis subsp. lactis.…”
Section: Introductionmentioning
confidence: 99%